An analysis of the U.S. meat industry from consumers' and processors’ points of view - Brouk, Matthias Reed (Kansas State University, 2023)
This thesis consists of two research papers on the meat industry focusing on locally processed meat. The first paper is based on a survey distributed to meat consumers throughout the U.S. with the objective of understanding their willingness to pay for locally processed meat. This goal was achieved with two economic models. The first was a Probit model to understand the likelihood of a consumer choosing to purchase meat as a portion of a carcass. The second was a bivariate Tobit model that was used to directly compare consumer purchasing levels between local and grocery providers. In the first paper, multiple results were discovered about the willingness to pay (WTP) of consumers for meat as both carcasses and cuts. For the probit model results, chicken was the most sensitive to price changes. Of the demographic variables analyzed, the one with the most significance in the purchase of carcasses was gender. Males were more likely to buy a carcass. Additionally, freezer space was positive and significant for the purchase of beef and pork carcasses. For the Tobit model, cross-price, and own prices elasticities for local and grocery were estimated across all the meat cuts and an average WTP were calculated. Across most of the cuts, there was little difference between grocery and local WTPs, and, in most models, grocery cuts had a larger WTP. For the demographic variables in the Tobit model, there was variation of statistical significance across all cuts, except for household size that presented a significant positive impact on the purchase of most cuts. The second paper is based on a survey distributed to meat processors throughout the U.S. with the goal of understanding processor interest in expansion and how it might line up with consumers’ willingness to pay from the first paper. The main finding from the survey was that the top barriers of expansion for the processors was employee availability and space and there was limited evidence of financial constraints for plant expansion. These discoveries have implications for U.S. local meat processors, especially the findings related to the willingness to pay for local that were lower across most cuts. Additionally, the research contributes to the literature regarding consumer behavior on meat purchases in the U.S. using a direct comparison of local and grocery cut WTP and combining it with processor expansion interest. The low WTP that was found for local means that small and median processors will need to make a profit by a different means if consumers are not willing to pay a premium. If there are not profits to be made from sales expansion will need to be made with care. The research also includes a presentation of the current state of a sample of U.S. meat processors and their expansion plans and finances, which are relevant aspects to consider given the consumer side findings and make this thesis an informative tool for processors, and policy makers interested on incentivize small meat processing. With processors not being financially constrained to expand, future support for processors may need to consider a different approach than financing.
Keywords: Willingness to pay; Meat processing; Local meat